Active nematics for living matter: from topological defects to tissue organisation - Ruske, LJ (2023)
Living matter describes systems which convert chemical energy from their surroundings to grow or to generate active forces. Biological tissues are composed of many anisotropic and active cells, which can exhibit nematic long-range orientational order. The continuous injection of energy on the single-cell level can lead to complex flow patterns on the tissue scale and topological defects in the cell orientation field. This thesis explores different applications of active nematic theories to living systems. By including key biological features in active hydrodynamic models, we investigate the interplay between collective flows, shape formation and topological defects in two- and three-dimensional tissues.